EFFECT OF PRESSURE ON CRYSTALLIZATION OF HIGH-ALUMINA AND MAGNESIAN BASALTS OF THE GREAT TOLBACHIK FISSURE ERUPTION, KAMCHATKA - Kadik A.A.; Rosenhauer M. (My University, 1987)
The question of whether subalkalic high-alumina and calcalkalic magnesian basalt: are derived from independent magmas or are the differentiation products of one parental magma has still not been settled. Nor is it clear whether the high-alumina and intermediate basalt varieties are differentiation products of magnesian basalt formed at pressures greater than 7 to 10 kb, at which, presumably, the liquidus phase of the latter basalt would be pyroxene. In view of this a study was made of the crystallization of magnesian and high-alumina basalts experimentally at pressures between 7.5 and 17 kb. Experimental data on the change in residual melt compositions during crystallization of magnesian basalt above 10 kb indicate that in the zone of pyroxene crystallization there exists a nearly linear dependence between the concentration of MgO and those of the other rock-forming oxides such as Al 2O 3 and CaO.